PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL RESTATEMENT PADA PERUSAHAAN DI INDONESIA - Desy Ismah Anggraini; Wiwiek Dianawati (Universitas Jember, 2017)
This study examines the influence of the number of boards of directors, proportion of independent commissioners and the frequency of audit committee meetings on financial restatement. The study used samples of listed companies ion Indonesia Stock Exchange (IDX) in all industries with excluding the financial industry, and the study period in 2012 to 2016. Result show that the number of board of directors and proportion of independent commissioners in company has a negative relationship to the restatement, but is not significant. The frequency of audit committee meetings has a positive and significant relationship, but is not in accordance with the research hypothesis. Keywords : restatement, boards of directors, independent commissioners, audit committee meetings